Multibeam seabed bathymetry of the Long-Term Ecological Research observatory HAUSGARTEN (Fram Strait) - Boris Dorschel; Simon Dreutter; Lilian Boehringer (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

In-situ Image Analysis of Habitat Heterogeneity and Benthic Biodiversity in the Prince Gustav Channel, Eastern Antarctic Peninsula - Peter M. Almond; Katrin Linse; Simon Dreutter; Susie M. Grant; Huw J. Griffiths; Rowan J. Whittle; Melanie Mackenzie; William D. K. Reid (Frontiers in Marine Science, 2021)
Habitat heterogeneity is important for maintaining high levels of benthic biodiversity. The Prince Gustav Channel, on the Eastern Antarctic Peninsula, is characterized by an array of habitat types, ranging from flat, mud-dominated sheltered bays to steep and rocky exposed slopes. The channel has undergone dramatic environmental changes in recent decades, with the southern end of the channel permanently covered by the Prince Gustav Ice Shelf until it completely collapsed in 1995. Until now the marine benthic fauna of the Prince Gustav Channel has remained unstudied. A shallow underwater camera system and Agassiz trawl were deployed at different locations across the channel to collect information on habitat type and heterogeneity, benthic community composition and macrofaunal biomass. The texture of the seafloor was found to have a significant influence on the benthos, with hard substrates supporting higher abundances and diversity. Suspension and filter feeding organisms, including porifera, crinoids, and anthozoans, were strongly associated with hard substrates, with the same being true for deposit feeders, such as holothurians, and soft sediments. Habitat heterogeneity was high across the Prince Gustav Channel, particularly on a local scale, and this was significant in determining patterns of benthic composition and abundance. Other physical variables including depth and seafloor gradient played significant, interactive roles in determining composition potentially mediated through other processes. Sites that were once covered by the Prince Gustav Ice Shelf held distinct and unique communities, suggesting that the legacy of the ice shelf collapse may still be reflected in the benthos. Biomass estimations suggest that critical thresholds of vulnerable marine ecosystem indicator taxa, as defined by the Commission for the Conservation of Antarctic Marine Living Resources, have been met at multiple locations within the Prince Gustav Channel, which has implications for the future establishment of no take zones and marine protected areas within the region.